2005
DOI: 10.1002/path.1783
|View full text |Cite
|
Sign up to set email alerts
|

High numbers of tumour‐infiltrating activated cytotoxic T lymphocytes, and frequent loss of HLA class I and II expression, are features of aggressive B cell lymphomas of the brain and testis

Abstract: Loss of both HLA class I and class II expression in B cell lymphomas is a mechanism of escape from a cytotoxic T lymphocyte (CTL) immune response and will therefore give a strong selective survival advantage in tumours expressing strong immunogenic antigens. We investigated loss of HLA expression using specific antibodies on tissue sections from 254 B cell lymphomas originating from nodal and different extranodal sites in relation to numbers of tumour-infiltrating T cells. Complete loss of HLA class I and II w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
(62 reference statements)
0
58
0
1
Order By: Relevance
“…In both IP-DLBCL subtypes, small homozygous deletions affected the HLA-DR and HLA-DQ genes, whereas larger hemizygous deletions affected the whole MHC region, including class I and III regions, as well. The specificity of this down-regulation in testicular DLBCL was confirmed in a recent immunohistochemical study on a large series of primary extranodal DLBCL presenting at various sites (7). In another recent study on predominantly primary nodal (non-IP) DLBCL, Rimsza et al (8) showed that loss of expression of HLA class II is highly discriminative for the clinical behavior of the disease and by far the most significant single prognostic factor.…”
mentioning
confidence: 82%
“…In both IP-DLBCL subtypes, small homozygous deletions affected the HLA-DR and HLA-DQ genes, whereas larger hemizygous deletions affected the whole MHC region, including class I and III regions, as well. The specificity of this down-regulation in testicular DLBCL was confirmed in a recent immunohistochemical study on a large series of primary extranodal DLBCL presenting at various sites (7). In another recent study on predominantly primary nodal (non-IP) DLBCL, Rimsza et al (8) showed that loss of expression of HLA class II is highly discriminative for the clinical behavior of the disease and by far the most significant single prognostic factor.…”
mentioning
confidence: 82%
“…The frequently observed loss of HLA-DQ, HLA-DR, and HLA-A due to homozygous or heterozygous 6p21.3 deletion (Table S1) may facilitate tumor-cell survival in organs characterized by a physiologically down-regulated immunophenotype. [27][28][29] Such loss of the HLA region has been suggested to be a prerequisite of lymphomas of immunoprivileged organs contributing to escape from the immune response. [27][28][29] In this regard, the observation of a patient with PCNSL and testicular relapse 8 years thereafter is of note; while both tumors carried identical IG gene rearrangements, the progressive loss of HLA expression on the tumor cells may have facilitated immune escape.…”
Section: Microenvironmentmentioning
confidence: 99%
“…[27][28][29] Such loss of the HLA region has been suggested to be a prerequisite of lymphomas of immunoprivileged organs contributing to escape from the immune response. [27][28][29] In this regard, the observation of a patient with PCNSL and testicular relapse 8 years thereafter is of note; while both tumors carried identical IG gene rearrangements, the progressive loss of HLA expression on the tumor cells may have facilitated immune escape. 30 A further unexplained issue relates to the preferential usage of the IGHV4-34 gene segment in PCNSL.…”
Section: Microenvironmentmentioning
confidence: 99%
“…This is substantiated by high numbers of infiltrating cytotoxic T cells in PCNSL and testicular DLBCL at the moment of clinical diagnosis. 6 In the case presented here, this infiltrate is more pronounced in the testicular relapse than in the CNS localisation. Under pressure of this immune reaction the ongoing remodelling of the idiotype, in addition to progressive loss of HLA class II and HLA class I expression, might thus provide escape mechanisms for the tumour cells, necessary for their sustained survival and growth at these sites.…”
Section: Discussionmentioning
confidence: 53%
“…3 A common aberration leading to immune escape of PCNSL and testicular DLBCL is loss of HLA expression. 4,5,6 Another common feature of both lymphoma types is a high level of (often ongoing) somatic hypermutation (SHM) in the immunoglobulin heavy chain (IgH) genes. 1,7,8 Although usually presenting with stage IE disease, patients with PCNSL or testicular DLBCL have a poor prognosis that has only recently improved upon introduction of novel chemotherapy strategies.…”
Section: From Brain To Testis: Immune Escape and Clonal Selection In mentioning
confidence: 99%